Evidence for an ηc(1S)π−resonance in B0→ηc(1S)K+π−decays - Aaij, R; Beteta, C; Adeva, B; Bjoern, M; Gruberg Cazon, B; Hadavizadeh, T; Hancock, T; Harnew, N; Hill, D; John, M; Jurik, N; Malde, S; et al. (SpringerOpen (part of Springer Nature), 2018)
A Dalitz plot analysis of B0→ηc(1S)K+π− decays is performed using data samples of pp collisions collected with the LHCb detector at centre-of-mass energies of s√=7, 8 and 13TeV, corresponding to a total integrated luminosity of 4.7 fb −1. A satisfactory description of the data is obtained when including a contribution representing an exotic ηc(1S)π− resonant state. The significance of this exotic resonance is more than three standard deviations, while its mass and width are 4096±20 +18−22MeV and 152±58 +60−35MeV, respectively. The spin-parity assignments JP=0+ and JP=1− are both consistent with the data. In addition, the first measurement of the B0→ηc(1S)K+π− branching fraction is performed and gives B(B0→ηc(1S)K+π−)=(5.73±0.24±0.13±0.66)×10−4, where the first uncertainty is statistical, the second systematic, and the third is due to limited knowledge of external branching fractions.